Gender diversity on boards for organizational impression management: An empirical study of Japanese firms. Issue 3 (12th May 2022) - Min, Jungwon
Abstract: The literature on gender diversity on corporate boards is growing, yet firms' motivation for achieving such diversity remains underexplored. This study examines the potential objective behind appointing female directors that could be driven by organizational impression management based on the hypothesis that firms strategically propose to nominate female directors when they need to form a favorable impression to their stakeholders, especially in relation to executive compensation. This study analyzed annual shareholders meeting agendas for 3585 listed Japanese firms between 2011 and 2020 and found that firms placed female director appointments on the meeting agenda when they needed approval for the revision of executive compensation. This tendency was strengthened for firms with more outside directors. This study's approach and findings contribute to the literature on corporate board gender diversity by suggesting organizational impression management as a potential strategic motivation behind the appointment of female directors.